Myofilament Calcium Sensitivity: Role in Regulation of In vivo Cardiac Contraction and Relaxation - Chung, Jae-Hoon; Biesiadecki, Brandon J.; Ziolo, Mark T.; Davis, Jonathan P.; Janssen, Paul M. L. (Frontiers in Physiology, 2016)
Myofilament calcium sensitivity is an often-used indicator of cardiac muscle function, often assessed in disease states such as hypertrophic cardiomyopathy (HCM) and dilated cardiomyopathy (DCM). While calcium sensitivity measurement provides important insights into the mechanical force-generating capability of a muscle at steady-state, the dynamic behavior of the muscle cannot be sufficiently assessed with a force-pCa curve alone. The dissociation constant (Kd) of the force-pCa curve depends on the ratio of the apparent on-rate (kon) and apparent off-rate (koff) of calcium on TnC and as a stand-alone parameter cannot provide an accurate depiction of the dynamic contraction and relaxation behavior without the additional quantification of kon or koff, or actually measuring dynamic twitch kinetics in an intact muscle. In this review, we examine the effect of length, frequency, and beta-adrenergic stimulation on myofilament calcium sensitivity and dynamic contraction, the effect of membrane permeabilization on calcium sensitivity, and the dynamic consequences of various myofilament protein mutations with potential implications in contractile and relaxation behavior.